TREND PENGGUNAAN E-LEARNING SEKOLAH MENENGAH KEJURUAN (SMK) DI RIAU - Ardiansyah, Muklas (JATISI, 2024)
Information technology is currently experiencing very rapid development in the world of education. Therefore, vocational schools in Riau also utilize information technology to carry out teaching and learning activities through the use of e-learning. The objectives of this research are (1) To evaluate and analyze the impact of implementing E-Learning through the Edmodo Platform (2) To identify factors that influence the effectiveness of E-Learning in improving students' understanding and learning achievement in Vocational High Schools. This type of research is qualitative with library research methods. This means that this research uses library materials as the main data source. Data collection was carried out by searching and reviewing various literature related to the study theme. The results of this research are Trends in the Use of E-Learning at Vocational High Schools (SMK) in Riau providing evidence and easy benefits for information technology users. There are advantages and disadvantages in implementing e-learning as a learning medium. The advantages of implementing e-learning include more economical costs, easy access, efficiency, interactive, collaborative and flexible. And the shortcomings of implementing e-learning such as the teaching and learning process tends to lead to training rather than education, the internet connection must be in good condition and the changing role of a teacher from previously mastering conventional learning techniques.